2014
DOI: 10.2174/1874434601408010056
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Women’s Experiences of Asthma Care in Pregnancy: A Qualitative Study

Abstract: Background : Most asthmatic women have normal pregnancies and complications are infrequent when their asthma is well-controlled. Symptom control and medical treatment are concerning to pregnant asthma suffers, as is the impact that their illness and treatment might have on their unborn baby. The aim was to investigate in a qualitative study the thoughts and feelings of women’s experiences of asthma in pregnancy. Twenty-two women with asthma who had a pregnancy within two years were asked to participate. Seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…The final papers included in the review consisted of two qualitative papers (see Table 3 ) that scored 90% [ 19 ] and 100% [ 14 ] respectively, and three quantitative papers (see Table 4 ) with scores ranging between 86 and 96%. The authors decided to include all papers scoring 60% or above, with only two papers in the initial assessment process not meeting this quality standard.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The final papers included in the review consisted of two qualitative papers (see Table 3 ) that scored 90% [ 19 ] and 100% [ 14 ] respectively, and three quantitative papers (see Table 4 ) with scores ranging between 86 and 96%. The authors decided to include all papers scoring 60% or above, with only two papers in the initial assessment process not meeting this quality standard.…”
Section: Resultsmentioning
confidence: 99%
“…Lim et al [ 19 ] and Chamberlain et al [ 14 ] conducted interview-based qualitative research with purposive samples of women (23 and seven participants respectively). Chamberlain et al [ 14 ] interviewed women who had delivered their babies within two years of the interview, using ‘Framework Analysis’ to construct themes from the qualitative data they recorded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar qualitative study was reported from the UK, in which seven women with asthma who had been pregnant within the previous 2 years were interviewed [ 33 ]. Four of these seven women reported a worsening of asthma symptoms during pregnancy, and these women expressed feelings of fear, panic and anxiety surrounding exacerbations, and a lack of understanding that some of their symptoms were due to asthma rather than the pregnancy itself.…”
Section: Experiences Of Pregnant Women In Relation To Asthma Managemementioning
confidence: 90%
“…The perception was that midwives did not know much about asthma and concentrated more on issues surrounding the pregnancy. In addition, two women described delays in obtaining care when they had exacerbations of asthma requiring admission to hospital [ 33 ]. More work is needed to clarify the priorities of pregnant women themselves with regard to their asthma management in pregnancy.…”
Section: Experiences Of Pregnant Women In Relation To Asthma Managemementioning
confidence: 99%